Physician liability for procedure related injury: Focused on central venous catheterization. (July 2015) - Lee, Seok-Bae; Bae, Hyuna; Kim, Sung Eun
Abstract: Central venous catheterization (CVC) is one of essential procedures in critical care medicine. CVC is relatively safe when performed by experienced physicians. Complications may occur due to various risk factors. Although the incidence of CVC-related complications is not high, a serious risk may ensue in cases of such complications. Procedure related complications could lead to civil and criminal lawsuits. This study reviewed the occurrence patterns and rulings of the courts related to CVC in South Korea and tried to find pitfalls that medical professionals should keep in mind before, during and after medical procedures. Various patterns of CVC-related lawsuits have been raised. During the procedure, physicians should perform their duty considering risk factors such as patients' underlying diseases and age. In addition, before the procedure, physicians must obtain written consent for CVC from patients or their legal guardians including explanation of rare complications that could be lethal. After the completion of CVC, surveillance of anticipated complications including chest radiographs should be conducted for the immediate management of any possible complications. Highlights: Reviewed the occurrence patterns and results of malpractice lawsuit related with CVC. Pitfalls that will help prevent future medico-legal problems. Physicians should consider risk factors such as patients' underlying diseases, age. Physicians must obtain written consent for CVC from patients or legal guardians. Post-procedural radiologic confirmation is associated with decreased indemnity risk.